Mucosal leishmaniasis in a patient with leprosy: a case report - Sacramento, Lorena; Abbehusen Couto, Larissa; Nunes dos Santos, Jean; Arruda, Sérgio Marcos; Carrera, Manoela (Journal of Oral Diagnosis, 2024)
Leishmaniasis and leprosy comprise the group of granulomatous diseases. Although both diseases have a known occurrence in Brazil, their concurrent presence is rare, and few cases have been reported in the literature. We report the case of a 46-year-old male patient co-infected with leprosy and mucosal leishmaniasis. Examination revealed an ulcerated lesion on the nose and a lesion with a granulomatous surface on the palate, in addition to spots on the arms and legs. After diagnosis, the patient was treated for co-infection and has been under follow-up for 2 years without signs of recurrence. The diagnosis of leishmaniasis/leprosy co-infection is challenging because of the broad clinical spectrum. Few cases have been reported in the literature and the dentist may play an important role in its detection.